Jim Flores, ControlTrix : a newly-installed vice-president of strategy tries to make sense of his company's human resource policies - Elias, Jaan (SAGE knowledge. Cases., 2016)
This case is written as a fictional journal by someone working in human resource management and details a number of conflicts that he encounters through his work.